Biosorption of Cr(VI) by a Bacillus coagulans biofilm supported on granular activated carbon (GAC) - Quintelas, C. (2008)
The ability of a biofilm of Bacillus coagulans supported on granular activated carbon (GAC) to biosorb Cr(VI) was investigated in batch and column studies so it may be applied to low metal concentration wastewater treatment. The quantification of polysaccharides and polymeric net revealed a value of 9.19 mg/gbiosorbent for the polysaccharides and 75 mg/gbiosorbent, for the polymeric net. The results obtained with open systems showed uptake values of 1.50, 1.98 and 5.34 mg/gbiosorbent, respectively, for initial concentrations of 10, 50 and 100 mg/L of Cr(VI). Column studies performed with an industrial effluent showed values of Cr uptake of 0.090 mg/gbiosorbent, for an initial concentration of 4.2 mg/L. The presence of functional groups on the cell wall surface of the biomass that may interact with the metal ion, was confirmed by FTIR. The equilibrium studies in batch systems were described by Freundlich, Langmuir, Reddlich–Peterson, Dubinin–Radushkevich, Sips and Toth model isotherms. Best fit was obtained with Toth model isotherm. Data from column studies were described by Adams–Bohart and Wolborska models. These models were found suitable for describing the dynamic behaviour of the columns with respect to the inlet chromium concentration. The whole study showed that the biofilm tested is very promising for the removal of Cr(VI) in industrial wastewater.